2021
DOI: 10.3390/cancers13051001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Channel RF Supervision Module for Thermal Magnetic Resonance Based Cancer Therapy

Abstract: Glioblastoma multiforme (GBM) is the most lethal and common brain tumor. Combining hyperthermia with chemotherapy and/or radiotherapy improves the survival of GBM patients. Thermal magnetic resonance (ThermalMR) is a hyperthermia variant that exploits radio frequency (RF)-induced heating to examine the role of temperature in biological systems and disease. The RF signals’ power and phase need to be supervised to manage the formation of the energy focal point, accurate thermal dose control, and safety. Patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Recognizing the opportunities of adding a thermal intervention dimension to an MRI device for studying the role of temperature in biological systems and disease our high‐density RF array opens a trajectory to an integrated, multi‐purpose RF applicator. This applicator accommodates RF‐induced heating, in vivo temperature mapping using MR thermometry, anatomic and functional MRI, and the option for x‐nuclei MRI (Thermal MR) 56‐61 . Potential clinical applications extend beyond diagnostic cardiac imaging and can serve as a platform to treat cardiovascular diseases, where localized RF intervention might be used, eg, terminate defective electrical pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the opportunities of adding a thermal intervention dimension to an MRI device for studying the role of temperature in biological systems and disease our high‐density RF array opens a trajectory to an integrated, multi‐purpose RF applicator. This applicator accommodates RF‐induced heating, in vivo temperature mapping using MR thermometry, anatomic and functional MRI, and the option for x‐nuclei MRI (Thermal MR) 56‐61 . Potential clinical applications extend beyond diagnostic cardiac imaging and can serve as a platform to treat cardiovascular diseases, where localized RF intervention might be used, eg, terminate defective electrical pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This applicator accommodates RF-induced heating, in vivo temperature mapping using MR thermometry, anatomic and functional MRI, and the option for x-nuclei MRI (Thermal MR). [56][57][58][59][60][61] Potential clinical applications extend beyond diagnostic cardiac imaging and can…”
Section: Discussionmentioning
confidence: 99%
“…This approach also suffers from compatibility issues and practical obstacles because each sub-device is provided by a different vendor. Thermal magnetic resonance (ThermalMR) integrates RF-induced heating in the HT range, in vivo non-invasive temperature mapping using MR thermometry (MRTh), and anatomical and functional MRI (and even physiometabolic MRI) in a single, multi-purpose RF applicator permitting supervised thermal theranostics [ 37 , 41 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. ThermalMR adds a therapeutic dimension to a diagnostic imaging device and has great promise to address the urgent need for novel personalized patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates that the proton resonance frequency shift method, i.e., the most common MRT method, can provide 3D temperature maps with around 0.5 °C accuracy [ 22 , 23 , 24 ]. For H&N hyperthermia, several studies [ 25 , 26 , 27 ] have shown the feasibility of adopting MR compatible applicators; however, to date, none of them has been adopted in clinical practice. Recently, we presented the novel MR compatible applicator for the H&N region: the MRcollar [ 15 ] equipped with a novel dual-function applicator concept [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%